Knowledge and Attitudes of Ugandan Midwives Regarding HIV - Salyer, Jennifer Lee Harling; Walusimbi, Mariam Louise; Fitzpatrick, Joyce J. (Journal of the Association of Nurses in AIDS Care, 2008)
In Uganda, 60% of HIV-infected adults are women of childbearing age. Considering this, midwives in Uganda play a pivotal role in reducing HIV transmission and providing high quality care to the many women and families affected by the disease. In this pilot study, investigators described the knowledge and attitudes of Uganda's private midwives regarding HIV. Overall knowledge levels were reported to be low, and the majority of participants reported overwhelming fear of contracting the disease from practice. Despite these challenges, the midwives' attitudes regarding HIV were positive. The results of this study support previous results. Additional studies focusing on midwives and traditional birth attendants in Uganda are warranted. The initiation of HIV continuing education programs and professional support for Ugandan midwives is also recommended.
Keywords: Africa; AIDS; attitude; fear; HIV; knowledge; midwifery; midwives; sub-Saharan; Uganda